Regulation of the use of facial recognition technology –limitations and challenges from a human rights perspective - Dokmanović, Mirjana (Teorija in praksa, 2023)
The aim of this article to identify and highlight limitations and challenges of the legal regulation of the use of facial recognition technology for surveillance purposes. The UN and the EU are seeking to develop robust human rights safeguards to regulate such practices, whereas civil society calls for a complete ban on it use for mass surveillance. The type of this technology makes it difficult to impose legal and democratic control over its lawful use and to prevent abuse. We conclude that the regulation of this area, no matter how restrictive, amounts to tacit approval of the mass use of this type of technology that opens the door to various ways of abusing human rights and freedoms, and whose justification from the perspective of the public interest is questionable.
Keywords: Clearview AI; Človekove pravice; facial recognition technology; Informacijsko-komunikacijska tehnologija; pravica do zasebnosti; prepoznavanje obraza; Prepoznavanje obrazov (računalništvo); protection of personal data; right to privacy; varstvo osebnih podatkov; video nadzor; video surveillance